Swarm Control for Multiple Unmanned Surface Vehicles with Unknown Time-Varying Environmental Disturbance and Input Saturation - Guoqing Xia; Xianxin Sun (Journal of Control Science and Engineering)
This paper addresses the swarm tracking problem of multiple unmanned surface vehicles subjected to unknown time-varying environmental disturbance and input saturation. The main control objective of this paper is that USVs cluster to follow the virtual leader with the desired position and heading and are required to maintain a specified position separation relative to both neighbor vehicles. In order to achieve the design goal, we mainly focus on three aspects. Firstly, to estimate the external disturbance accurately and improve the convergence speed, a finite-time disturbance observer is designed. Secondly, an auxiliary dynamic system is introduced to solve the input saturation problem. Thirdly, an output feedback controller based on a finite-time disturbance observer and an auxiliary dynamic system is designed to achieve swarm control of multiple unmanned surface vehicles. The stability of the system is proved by the Lyapunov directly method. Finally, the simulation results show that the proposed control strategy is effective.